Neuroplastin‐β mediates S100A8/A9‐induced lung cancer disseminative progression. Issue 6 (27th February 2019) - Sumardika, I Wayan; Chen, Youyi; Tomonobu, Nahoko; Kinoshita, Rie; Ruma, I Made Winarsa; Sato, Hiroki; Kondo, Eisaku; Inoue, Yusuke; Yamauchi, Akira; Murata, Hitoshi; Yamamoto, Ken‐ichi; Tomida, Shuta; et al.
Abstract : Compiling evidence indicates an unusual role of extracellular S100A8/A9 in cancer metastasis. S100A8/A9 secreted from either cancer cells or normal cells including epithelial and inflammatory cells stimulates cancer cells through S100A8/A9 sensor receptors in an autocrine or paracrine manner, leading to cancer cell metastatic progression. We previously reported a novel S100A8/A9 receptor, neuroplastin‐β (NPTNβ), which plays a critical role in atopic dermatitis when it is highly activated in keratinocytes by an excess amount of extracellular S100A8/A9 in the inflammatory skin lesion. Interestingly, our expression profiling of NPTNβ showed significantly high expression levels in lung cancer cell lines in a consistent manner. We hence aimed to determine the significance of NPTNβ as an S100A8/A9 receptor in lung cancer. Our results showed that NPTNβ has strong ability to induce cancer‐related cellular events, including anchorage‐independent growth, motility and invasiveness, in lung cancer cells in response to extracellular S100A8/A9, eventually leading to the expression of a cancer disseminative phenotype in lung tissue in vivo. Mechanistic investigation revealed that binding of S100A8/A9 to NPTNβ mediates activation of NFIA and NFIB and following SPDEF transcription factors through orchestrated upstream signals from TRAF2 and RAS, which is linked to anchorage‐independent growth, motility and invasiveness. Overall, our results indicate the importance of the S100A8/A9‐NPTNβ axis in lung cancer disseminative progression and reveal a pivotal role of its newly identified downstream signaling, TRAF2/RAS‐NFIA/NFIB‐SPDEF, in linking to the aggressive development of lung cancers.